Physiological response of marandu grass seeds exposed to npk fertilizer - Codognoto, Luciane Da Cunha; Conde, Thassiane Telles; Maltoni, Kátia Luciene [UNESP]; Faria, Glaucia Amorim [UNESP]; Dos Reis, André Rodrigues [UNESP] (FapUNIFESP (SciELO), 2019)
To facilitate seeding process of forage species, a common practice is to mix seeds with fertilizers in monocropping and intercropping or in implementing integrated livestock production systems. However, in prolonged periods of contact, the fertilizer’s salinity and acidity negatively affect the seeds’ physiological quality. Therefore, this study intends to verify the effect of ten periods (0, 3, 6, 12, 24, 36, 48, 72, 96, and 120 hours) of exposure to granular NPK fertilizer 04-30-16 on the vigor and germination of Urochloa brizantha cv. Marandu seeds. The experiment was conducted in a completely randomized design with three replication. The fertilizer and seed mixture registered a negative effect on seed moisture content, electrical conductivity, emergence, emergence speed index, and seedling and radicle length as the period of exposure to the fertilizer increased from 3 to 120 hours.
Resposta fisiológica de sementes de capim marandu expostas ao fertilizante NPK
Keywords: Brachiaria; Germination; Ionic effect; Osmotic effect; Salinity